Combining molecular and morphological data to test the monophyly of Hypotelus Erichson and description of new species from Ecuador (Coleoptera, Staphylinidae, Piestinae) - Caron, Edilson; Mcclarin, Jim; Buss, Bruna Caroline; Foti, Leonardo (Zootaxa, 2025)
Hypotelus Erichson is a genus of minute rove beetles widely distributed in Central and South America. The species were recently revised and the monophyly of the genus was confirmed based on morphological data. We describe a new species from Ecuador, provide scanning electron microscope images to demonstrate the diagnostic characteristics of the genus and include the new species in a dichotomous key. We also reassess the monophyly of the genus, now including the new species, using morphological and molecular data combined. Hypotelus chusqueaticus sp. nov. is similar to H. testaceus, but differs by having elytra unicolored, male sternite 8 with posterior margin somewhat pointed and female sternite 8 with posterior margin projected in middle-third. Including the new species, Hypotelus is confirmed as a monophyletic group with three internal clades. The new species is closely related to H. marginatus.